NEUROARSITEKTUR: PENDEKATAN ARSITEKTUR FUTURISTIK UNTUK RUANG KERJA GENERASI Z - Nadya Ananda Ramadani; Wendy Sunarya (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Neuroarchitecture is an approach that integrates neuroscientific knowledge with architectural design principles to create built environments that will support the well-being and productivity of its inhabitants. This paper debates primary concepts of neuroarchitecture – including its history and the four pillars of human well-being  that it carries with it – as well as its implications for designing futuristic workplaces supporting the mental health and creativity of Gen Z. It finally presents the psychological characteristics of Gen Z and its workplaces’ challenges  to emphasize the design’s need to focus on users’ emotional and biological aspects. As an empirical review, several real-case studies  are analyzed, such as Amazon Spheres in Seattle, Second Home Hollywood, Mr.Green’s Office in Brazil, applying neuroarchitecture principles, including natural lighting, biophilia elements, and space flexibility. Study results demonstrate that a concrete neuroarchitecture application can significantly enhance the comfort, collaboration, and innovation, resulting in Gen Z performance and mental health. This paper concludes that designing future workplaces for Gen Z will require a holistic approach, combining the excellence of technology with neuroscientific care for users.